P25 Distinct Pro-inflammatory Gene Expression Profile In Monocytes From Sarcoidosis Patients With Active Disease. (10th November 2014) - Crawshaw, AP; Kendrik, YR; Repapi, E; Taylor, S; Ho, L-P
Abstract : Introduction: Monocytes are potential key cellular players inthe early pathogenesis of sarcoidosis. Having previously identified altered monocyte activity in sarcoidosis, 1 we now examine monocyte whole genome expression profile in order to determine potential processes and pathways involved in the perturbed immune activity of these cells. Methods: Patients with tissue-confirmed sarcoidosis (three high-activity, three low-activity, identified by a predefined clinical activity score) 2 were recruited: gene expression profiles compared with age and gender matched healthy controls. All donors were Caucasian, corticosteroid (and other immunemodulatory treatment) naïvenon-smokers. Monocytes were isolated by CD14-negative magnetic selection within 3 h of venesection, RNA extracted using a proprietary kit and stored at -80°C prior to single batch hybridisation with Illumina HumanHT-12 v4 chips. Results: A total of 3437 genes were differentially expressed in sarcoidosis monocytes compared with controls (adjusted p value of <0.05). Filtering by Log2 fold change of at least1.5 identified 151 differentially expressed genes among these. Principal component analysis demonstrated clear segregation between sarcoidosis and controls, and between those with high and low activity, with low activity clustering closer to healthy controls. IL-6 was the most significantly upregulated gene (Log2 FC 4.723 adjusted p < 0.001). Other significantly upregulated genes included the pro-inflammatory cytokines IL1A (2.987, 0.001) and IL1B (2.952, 0.001); and the monocyte chemotactic factors CCL20 (4.212, 0.002), CXCL2 (4.057, <0.001) and CCL3 (3.470, 0.003). Gene set enrichment analysis identified gene ontology (GO) gene sets relating to inflammatory andimmune system responses to be amongst the most positively enriched genes in the monocytes from patients with active disease (p < 0.001, normalised enrichment score [NES] 2.22 and 2.20 respectively). Conclusions: Sarcoidosis monocytes sarcoidosis have a distinct gene expression profile exhibiting a pro-inflammatory, chemotactic phenotype. IL6 may be implicated in the initiation and maintenance of alveolitis and hypergammaglobulinemia in sarcoidosis and the recent interest in the use of humanised anti-IL-6R antibodies in the treatment of rheumatoid arthritis and other immune mediated disease makes functional characterisation of the role of IL-6 in the pathogenesis of sarcoidosis an exciting prospect. References: Crawshaw A et al . Eur J Immunol 2014 Kendrick YR et al . Am J Respir Crit Care Med 2013;187:A1391